1983
DOI: 10.1002/tea.3660200205
|View full text |Cite
|
Sign up to set email alerts
|

The myth of equality in science classrooms

Abstract: An analysis of the 1976‐1977 NAEP survey of science attitudes showed that, by age nine, females, although expressing similar or greater desires to participate in science activities, had consistently fewer experiences in science than boys of the same age. Science activities surveyed included use of common experimental materials and instruments, observation of scientific phenomena, and field trips. At ages 13 and 17, girls again reported fewer classroom and extracurricular science activities than boys. Their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
148
2
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(163 citation statements)
references
References 5 publications
8
148
2
3
Order By: Relevance
“…Finding by Mior (2002), Shaw (2003, Manganye (2007) andNur Asyiqin (2004) who found that there are no difference in interest towards Physics based on gender.There is difference in students' attitudinal variables towards career related to physics based on gender. The result findings in this study conform to the findings by Kahle and Lakes (1983) that female students showed negative attitude towards career related to Physics.…”
Section: Students' Attitude Towards Physics Based On Gendersupporting
confidence: 82%
See 1 more Smart Citation
“…Finding by Mior (2002), Shaw (2003, Manganye (2007) andNur Asyiqin (2004) who found that there are no difference in interest towards Physics based on gender.There is difference in students' attitudinal variables towards career related to physics based on gender. The result findings in this study conform to the findings by Kahle and Lakes (1983) that female students showed negative attitude towards career related to Physics.…”
Section: Students' Attitude Towards Physics Based On Gendersupporting
confidence: 82%
“…Male students tend to use science equipment's more and participated in activities related to science (Guzzetti & Williams, 1996). The findings by Kahle and Lakes (1983) showed that a higher number of female students gave a negative view of science and careers related to science. Majority of female students opined that science classes are boring and they only need to memorize facts to secure good grades whereas careers related to science are perceived as having to do a lot of work.…”
Section: Students' Attitude Towards Physics Based On Gendermentioning
confidence: 82%
“…This gender related difference in attitudes was considered to contribute to the lack of women in science fields (Kahle & Lakes, 1983). However, recent research reveals social factors contribute to the gender difference in attitudes towards science such as family support, peer support, school science characteristics, social factors, and science learning experiences (Brotman & More, 2008;Gilmartin & Aschbacher, 2006;Hazari et al 2010;Stake & Nickens, 2005).…”
Section: Students' Attitudes Toward Science and Their Career Choicesmentioning
confidence: 99%
“…Various studies have offered different reasons for this phenomenon, these including; poor teacher attitude, lack of investment, lack of community engagement and poor textbooks and educational material [5]. Gender and cultural issues were also highlighted as catalyst with some suggesting that although females and minority groups express similar or more interest in learning science and participating in science activities they are allowed less or experienced more limited opportunities than male cohorts, resulting in a narrower perspective of science and its usefulness [6]. In addition, socioeconomic dilemmas were also noted to decrease the uptake and investment in science careers [7] with students from lower socio-economic areas performing less well than those from middle class localities.…”
Section: Introductionmentioning
confidence: 99%